The Relationship Energy Sources Use-CO2 Emissions and Economic Growth: An Investigation on Developing Economies - Mustafa Yapar (İstanbul İktisat Dergisi)
Energy and all concepts related to energy are factors that affect the economic growth level of countries. When energy is examined in terms of developing economies, it is understood how vital energy is. Increasing energy demand is affected by various dynamics that affect the strategies and policies ofcountries. Since energy is an input for production, it is a determinant of the economic growth process. It is important to consider the resources used while assessing the energy required in production. There are two types of energy sources: renewable and non-renewable. Regarding the future of the world and the use of fossil fuels, there are concerns about climate change and global warming. It is seen that international cooperation on this issue is inevitable. In this paper, the relationship between energy use, CO2 emissions, and economic growth are analyzed for selected developing economies. The study examines the connections between the consumption of renewable and non-renewable energy, CO2 emissions per capita, and capita income between 1995 and 2014. Selecting the data for this period is due to the desire to include more developing economies in the model. Finally, it has been determined that all three independent variables have a positive effect on economic growth. In order to combat climate change, it is important for developing economies to encourage renewable energy for a sustainable life.